Effect of focused ion beam machining parameters on geometrical accuracy of Bio-MEMS - Nurul Hajar binti Mohd Fuad (Kulliyyah of Engineeering, International Islamic University Malaysia, 2011)
This thesis introduced focused ion beam (FIB) micromachining as a potential technique to fabricate Bio-MEMS microfluidic devices. This work investigated the influence of three FIB process parameters, which were acceleration voltage, dwell time and milled depth. The response variables were taper angle (θ), aspect ratio (ar) and average surface roughness (Ra). Statistical models of output responses were developed using Taguchi method of design of experiment. Signal to noise ratio were calculated and analyzed for all of the responses. S/N ratio showed that, responses of θ and ar were influenced by milled depth followed by dwell time and acceleration voltage. On the other hand, dwell time gives higher impact on Ra compared to acceleration voltage and milled depth. Developed models by analysis of variance (ANOVA) were used for multiple local response optimizations by desirability function approach to obtain minimum θ, Ra and maximum ar. The optimized values were obtained and verified experimentally. The optimized values of θ, ar were 7.5° and 1.7 respectively which were obtained at acceleration voltage of 20 keV, dwell time of 15 μs and milled depth of 5 μm. Besides, the optimized values of Ra 13.7 nm was obtained at acceleration voltage of 20 keV, dwell time of 15 μs and milled depth of 0.6 μm. Verification of optimized results showed 2–9 % errors. By using these options of process parameters, microfeatures for Bio-MEMS were fabricated on silicon wafer substrate. This includes micropillars and microholes array for application in microfluidics or cell culture. Diameter of 1.7-2.4 μm of microholes and micropillar were fabricated with 2-4 of aspect ratio. Microhole array of diameter 2.4 μm was fabricated on silicon which can be used as filter or micromold master for replication of polymer micropillars. Besides, fabricated micropillars array of pillar diameter 1.7 μm can be utilized as cell culture dish for biomedical applications.